2011
DOI: 10.1016/j.ica.2011.01.070
|View full text |Cite
|
Sign up to set email alerts
|

A merged experimental and theoretical conformational study on alkaline-earth complexes with lariat ethers derived from 4,13-diaza-18-crown-6

Abstract: a b s t r a c tHerein, we report the synthesis and structural characterization of alkaline-earth complexes with the bibracchial lariat ethers N,N 0 -bis(2-aminobenzyl)-4,13-diaza-18-crown-6 (L 2 ) and N,N 0 -bis(benzimidazol-2ylmethyl)-4,13-diaza-18-crown-6 (L 4 ). The X-ray crystal structures of the Ca(II) and Sr(II) complexes of L 2 show the pendant arms of the ligand disposed on opposite sides of the macrocyclic mean plane, which results in an anti conformation in the solid state. A similar anti conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
2
7
0
Order By: Relevance
“…The 1 H NMR spectra of the complexes of L 3 and L 4 show essentially the same features than those of the L 1 and L 2 counterparts, but they show broader signals, particularly for L 3 complexes. A similar situation was observed previously when comparing the 1 H spectra of the complexes of L 5 and L 6 [24] . This indicates a more important degree of flexibility of the complexes containing aniline pendants in comparison to those with benzimidazole arms.…”
Section: Nmr Spectroscopysupporting
confidence: 87%
See 2 more Smart Citations
“…The 1 H NMR spectra of the complexes of L 3 and L 4 show essentially the same features than those of the L 1 and L 2 counterparts, but they show broader signals, particularly for L 3 complexes. A similar situation was observed previously when comparing the 1 H spectra of the complexes of L 5 and L 6 [24] . This indicates a more important degree of flexibility of the complexes containing aniline pendants in comparison to those with benzimidazole arms.…”
Section: Nmr Spectroscopysupporting
confidence: 87%
“…This in contrast with structures observed in the solid state for the Ca(II) and Sr(II) complexes of L 6 , which present an anti conformation of the ligand. Both the complexes of L 5 and L 6 exist in acetonitrile solution as a mixture of syn and anti conformers [24] . Table 8.…”
Section: B a 2b 3b 4bmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] Therefore, we aimed here to develop a novel fluorescent sensor that had high sensitivity and selectivity for Mg 2+ ion detection. In recent years, the details of several Mg 2+ selective fluorescent sensors have been published, such as crown ether derivatives, [28] imidazo-1,10-phenanthroline, [29] benzochromene, [30] diaza-18-crown-6, [31] and benzo-15-crown-5, [32] therefore the design of novel fluorescence sensors that have the advantages of high sensitivity and selectivity of Mg 2+ in different media remains an important task. Azothiazol-benzenesulfonamide derivatives containing thiazol and benzene sulfonamide associated with the azo group (ÀN=N-) are classified into three organic families: sulfonamide, azo, and pyrazole.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we reasoned that the investigation of chelators with a reverse size-selectivity, a preference for large over small ions, would be a promising direction for the development of new BFCs for this radionuclide. In this context, ligands containing the 18-membered diaza-18-crown-6 macrocycle display this reverse size-selective property for metal ions. Previously, we showed that macropa (Chart ) forms remarkably stable complexes with large medicinally relevant radiometals like 132/135 La, 223 Ra, and 225 Ac. ,, We further showed that alteration of the pendent donor arms and macrocyclic core rigidity changes the resulting selectivity for different metal ions. ,, On the basis of the reverse size-selectivity properties and tunability of this system, we sought to explore this class of ligands (Chart ) for chelating Bi 3+ for potential applications in TAT.…”
Section: Introductionmentioning
confidence: 99%